Functional recovery is considered the most important target: a survey of dedicated professionals - Aahlin, Eirik K.; von Meyenfeldt, Maarten; Dejong, Cornelius H.C.; Ljungqvist, Olle; Fearon, Kenneth C.; Lobo, Dileep N.; Demartines, Nicolas; Revhaug, Arthur; Wigmore, Stephen J.; Lassen, Kristoffer (BioMed Central, 2014)
Background: The aim of this study was to survey the relative importance of postoperative recovery targets and perioperative care items, as perceived by a large group of international dedicated professionals. Methods: A questionnaire with eight postoperative recovery targets and 13 perioperative care items was mailed to participants of the first international Enhanced Recovery After Surgery (ERAS) congress and to authors of papers with a clear relevance to ERAS in abdominal surgery. The responders were divided into categories according to profession and region. Results: The recovery targets ‘To be completely free of nausea’, ‘To be independently mobile’ and ‘To be able to eat and drink as soon as possible’ received the highest score irrespective of the responder's profession or region of origin. Equally, the care items ‘Optimizing fluid balance’, ‘Preoperative counselling’ and ‘Promoting early and scheduled mobilisation’ received the highest score across all groups. Conclusions: Functional recovery, as in tolerance of food without nausea and regained mobility, was considered the most important target of recovery. There was a consistent uniformity in the way international dedicated professionals scored the relative importance of recovery targets and care items. The relative rating of the perioperative care items was not dependent on the strength of evidence supporting the items.